Risk factors for neonatal encephalopathy in Kathmandu, Nepal, a developing country: unmatched case-control study. Issue 7244 (6th May 2000) - Ellis, Matthew; Manandhar, Nilu; Manandhar, Dharma S; Costello, Anthony M de L
Abstract: Objective: To determine the risk factors for neonatal encephalopathy among term infants in a developing country. Design: Unmatched case-control study. Setting: Principal maternity hospital of Kathmandu, Nepal. Subjects: All 131 infants with neonatal encephalopathy from a population of 21 609 infants born over an 18 month period, and 635 unmatched infants systematically recruited over 12 months. Main outcome measures: Adjusted odds ratio estimates for antepartum and intrapartum risk factors. Results: The prevalence of neonatal encephalopathy was 6.1 per 1000 live births of which 63% were infants with moderate or severe encephalopathy. The risk of death from neonatal encephalopathy was 31%. The risk of neonatal encephalopathy increased with increasing maternal age and decreasing maternal height. Antepartum risk factors included primiparity (odds ratio 2.0) and non-attendance for antenatal care (2.1). Multiple births were at greatly increased risk (22). Intrapartum risk factors included non-cephalic presentation (3.4), prolonged rupture of membranes (3.8), and various other complications. Particulate meconium was strongly associated with encephalopathy (18). Induction of labour with oxytocin was associated with encephalopathy in 12 of 41 deliveries (5.7). Overall, 78 affected infants (60%) compared with 36 controls (6%) either had evidence of intrapartum compromise or were born after an intrapartum difficulty likely to result in fetal compromise. A concentration of maternal haemoglobin of less than 8.0 g/dl in the puerperium was significantly associated with encephalopathy (2.5) as was a maternal thyroid stimulating hormone concentration greater than 5 mIU/l (2.1). Conclusions: Intrapartum risk factors remain important for neonatal encephalopathy in developing countries. There is some evidence of a protective effect from antenatal care. The use of oxytocin in low income countries where intrapartum monitoring is suboptimal presents a major risk to the fetus. More work is required to explore the association between maternal deficiency states and neonatal encephalopathy.